2017
DOI: 10.1097/txd.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fc-γ Receptor Polymorphism on Rituximab-Mediated B Cell Depletion in ABO-Incompatible Adult Living Donor Liver Transplantation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
1
17
1
Order By: Relevance
“…Studies indicated that allelic polymorphisms in CD32A may correlate with the efficacy of immunoglobulin-based therapeutics according to their variable affinity for immunoglobulins. It was also suggested that the therapeutic response to rituximab (anti-CD20 monoclonal antibody) [35][36][37] is associated with the CD32A genotype, while FcγRs may have an effect on intravenous IgG-related immunomodulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that allelic polymorphisms in CD32A may correlate with the efficacy of immunoglobulin-based therapeutics according to their variable affinity for immunoglobulins. It was also suggested that the therapeutic response to rituximab (anti-CD20 monoclonal antibody) [35][36][37] is associated with the CD32A genotype, while FcγRs may have an effect on intravenous IgG-related immunomodulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…20-22 In organ transplantation, to our knowledge, only one study reported the effect of Fc-γ receptor polymorphism on rituximab-mediated B-cell depletion for complications after ABO-incompatible liver transplantation. 23 The analysis of gene polymorphism also in kidney transplant recipients before desensitization using rituximab may be useful for prediction of the AMR risk after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in ABO-incompatible living donor liver transplantation that SNPs of the Fc fragment of IgG receptor (FCGR) gene may influence the risk of infection following Rituximab in this setting. 95 Indeed certain genotypes in this region have also been shown to correlate with clinical and molecular responses to Rituximab in non-Hodgkins lymphoma. 96 The significance of this phenomena on B-cell depletion in renal transplant induction has yet to be established.…”
Section: Induction Therapymentioning
confidence: 99%